Cultural tradition of ancient Mongols in the Secret History of the Mongols - Serjee, Munkhsaikhan (Studia Folclorica, 2024)
The Secret History of the Mongols contains extensive evidence of Mongolian customs and cultural practices. These findings suggest that oral traditions such as “oral decrees”, “oral news”, “oral agreements”, “oral oaths”, and “oral lessons”—played a significant role in society. Such traditions were essential cultural pillars that embodied values of integrity, upbringing, and courage. This is reflected in the medieval Mongolian saying, "Don’t Mongols have an oath of ‘za’ (meaning ‘yes’)?" Additionally, sections detailing wedding customs, which have been passed down since ancient times, provide valuable insights. Traditions such as betrothal, formally requesting a bride’s hand in marriage, taking a wife, and granting a daughter in marriage as an honor were not merely aspects of population planning. Rather, they served as mechanisms for maintaining social harmony and ensuring peaceful coexistence. Similarly, the study suggests that Mongolian customs played a fundamental role in structuring and regulating social relations in an orderly manner. Regarding mentalities, the foundation of Mongol unity in consciousness and worldview lay in their shared belief in “Munkh Tenger (the Eternal Sky)” and shamanistic customs dedicated to nature. This was not merely a religious transformation but also a profound shift in the way medieval Mongols perceived and understood the world. Монголын нууц товчоон дахь эртний монголчуудын соёлын уламжлал Хураангуй: Монголын нууц товчоо хэдийгээр дундад зууны монголчуудын төрт улсаа байгуулсан түүхэн үйл явдлыг тэмдэглэн үлдээсэн төрийн түүх боловч түүнд эртний монголчуудын соёлтой холбоотой олон баримт хадгалагдан байдаг. Үүнийг бид эртний монголчуудын аман соёл, харилцааны соёл, ураг хуримын соёл, шашин шүтлэгийн соёл хэмээн хуваан тус бүрд нь судалж үзэв. Судалгааг дүгнэн үзвэл, эртний монголчуудын бүтээн бий болгосон соёл, ёс заншил нь эртнээс нааш уламжлагдан ирж, нийгмийн харилцааг эмх цэгцтэй, дэг журамтай болгодог бичигдээгүй журам байжээ. Өөрөөр хэлбэл, эртний монголчуудын соёлоор дамжсан дадал зуршил нь нийгмийн харилцаа болоод өдөр тутмын амьдралыг эмх журамтай болгож, тэрхүү өдөр тутмын амьдралын дадал хэвшлээр дамжуулан хүнийг хүмүүжүүлэн төлөвшүүлэх, ёс суртахуун, харилцааны хандлагад сургадаг, товчоор хэлбэл хүнийг “хүн” болгодог гол зүйл байжээ. Түлхүүр үг: Монголын нууц товчоо, аман соёл, харилцааны соёл, ураг хуримын соёл, шашин шүтлэгийн соёл